MENGEMBANGKAN SISTEM KOMPENSASI BERBASIS KINERJA DI RUMAH SAKIT HARAPAN MAGELANG - Tri Juli Wati; Sugianto Adisaputro; Andreasta Meliala (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: Harapan Hospital has started performance appraisal toward employees since 2010. The result of these performance appraisal become the base for the following year's payment. Within five years of performance appraisal, the result hasn't improved, but decreased instead. On the other side, employee's salary continuously increased. So, we can say that the compensation which is received by the employee isn't relevant with their performance appraisal, and doesn't affect the performance's improvement, therefore evaluations and improvements on the recent compensation system are necessary.Objective: The goal of this research was to develop aperformance-based compensation system in Harapan HospitalMagelang.Methods: This research is a case study research with a casestudy research design type 1, which means holistic single casedesign.Results: Four factors that based the completeness of the PayModel as the foundation of the payment structure, is yet to befulfifilled by the recent payment system. Performance appraisalthat have been used so far is incapable of pushing betterperformance, because the guide used during the performanceappraisal are too subjective that it can't diffffer each employee'scapabilities. Performance appraisal results today become thebase of the employee's salary, and this caused uncertaintyabout the salary changes. Incentive is being given equally. Theperception of compensation system and its component are stillyet to be well understood by neither the company nor theemployee. There is still yet to be any agreement in formulatingperformance-based compensation system because of theemployee's pessimistic behaviour and their thought, whichconsiders performance appraisal nothing more than routines forformality.Conclusion: The completeness of Pay Model is yet to be basedon performance based compensation system which are stillvalid, so more evaluations and improvements have to be done,which would resulted with a reliable compensation structure thatcan be formulated and able to become an attraction for potentialemployees as well as becoming a pushing factor forperformance's improvement.